2009
DOI: 10.1007/s11249-009-9465-z
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Methyl Group at C2 Position in Imidazolium Ring on Tribological Properties

Abstract: Tribological properties of two kinds of imidazolium ionic liquids (ILs) of 1,2-dimethyl-3-hexylimidazolium bis(trifluoromethylsulfonyl)imide (L-F116) and 1-dimethyl-3-hexylimidazolium bis(trifluoromethylsulfonyl)imide (L-F106) were evaluated as lubricant additives in poly(ethylene glycol) (PEG) for the steel-steel sliding pair by using an Optimol-SRV oscillating friction and wear test at the room temperature. At the same time, their electrochemical corrosion behaviors were measured by Tafel polarization. The m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 29 publications
0
28
0
Order By: Relevance
“…Figure 10 gives the XPS spectra of the typical elements on the rubbed surface lubricated with the grease containing different solid additives. The broad O1s peak indicates that the worn surfaces have complex oxide species [11].The weak single of B1s peak at 192.6 eV (Fig. 10b) was assigned to B 3 O 5 [12].…”
Section: Sem and Xps Analysis Of The Worn Surfacementioning
confidence: 97%
“…Figure 10 gives the XPS spectra of the typical elements on the rubbed surface lubricated with the grease containing different solid additives. The broad O1s peak indicates that the worn surfaces have complex oxide species [11].The weak single of B1s peak at 192.6 eV (Fig. 10b) was assigned to B 3 O 5 [12].…”
Section: Sem and Xps Analysis Of The Worn Surfacementioning
confidence: 97%
“…Numerous studies refer the better solubility of ILs in polar base oils such as ester [41][42][43], polyethylene glycol [44][45][46], or glycerol [47][48][49]. But corrosion is also an important issue in industry [50,51], being closely related to lubrication.…”
Section: Introductionmentioning
confidence: 99%
“…Jimenez and Bermudez studied the tribological properties of several ILs as additives in paraffinic-naftenic mineral base oil and synthetic esters and found that highly polar ILs could reduce both friction and wear with respect to the base oil [33][34][35]. Yao et al [36,37] synthesized and evaluated several imidazolium ILs as anti-wear additives in poly(ethylene glycol). Their results show that these could effectively reduce the friction and wear of sliding pairs compared with cases in which additives were not used.…”
Section: Introductionmentioning
confidence: 99%